2010 International Conference on Science and Social Research (CSSR 2010) 2010
DOI: 10.1109/cssr.2010.5773905
|View full text |Cite
|
Sign up to set email alerts
|

The level of patience and confidence towards problem solving and mathematics achievement of students in a technical institute

Abstract: The purpose of this study is to explore the level of patience and confidence towards problem solving and mathematics achievement among students from Malaysian Institute of Information Technology, Universiti Kuala Lumpur. This study also observes the relationship between the level of patience and confidence towards problem solving and mathematics achievement. This research is a survey study that is conducted on 121 semester one students at diploma and bachelor program. This research uses one set of questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
0
11
0
3
Order By: Relevance
“…The results of the self-confidence assessment are in accord with the results of a metaanalysis conducted by Hyde et al (1990), which showed that male subjects had moderately higher maths self-confidence than female subjects. It should be emphasized that gender differences in self-confidence were not found in one part of the related research (Mohd et al, 2011;Yeo et al, 2015). A possible explanation for the gender differences in the confidence variable could be that the strategies and methods used in the teaching process were not equally appropriate for boys and girls.…”
Section: Resultsmentioning
confidence: 93%
“…The results of the self-confidence assessment are in accord with the results of a metaanalysis conducted by Hyde et al (1990), which showed that male subjects had moderately higher maths self-confidence than female subjects. It should be emphasized that gender differences in self-confidence were not found in one part of the related research (Mohd et al, 2011;Yeo et al, 2015). A possible explanation for the gender differences in the confidence variable could be that the strategies and methods used in the teaching process were not equally appropriate for boys and girls.…”
Section: Resultsmentioning
confidence: 93%
“…Meskipun banyak faktor yang mempengaruhi prestasibelajar matematika, sebagian besar penelitian di negara-negara ASEAN berfokus pada faktor peserta didik. Namun, para ahli juga mengungkap bahwa prestasi belajar peserta didik dalam matematika turut dipengaruhi oleh sikap terhadap pemecahan masalah matematika [3].…”
Section: Pendahuluanunclassified
“…Measuring the attitude has become very vital in the field of education as relationship is observed between students' performance and their attitude towards mathematics (Marchis, 2013;Mohd, Mahmood & Ismail, 2011). Students with a positive attitude towards Mathematics have better problem solving skills and like more to solve non-routine problems (Marchis, 2013).…”
Section: Introductionmentioning
confidence: 99%